Do silvopastoral management practices affect biological pest control in oil palm plantations? - Nobilly, Frisco; Sharifah Nur Atikah; Yahya, Muhammad Syafiq; Jusoh, Shokri; Maxwell, Thomas M. R.; Norhisham, Ahmad Razi; Tohiran, Kamil Azmi; Raja Zulkifli; Azhar, Badrul (Institute for Ionics, 2023)
The reliance of conventional oil palm production on agrochemicals to control understory vegetation has caused devastating impacts on the environment. Overuse of chemical herbicides leads to the decline of native biodiversity and production-related ecosystem services, including biological pest control. In contrast to herbicide applications, livestock integration is a chemical-free approach to eradicate weeds without negative consequences on the environment. In this sentinel prey experiment, we assessed the predation pressure (based upon the number of bite marks left by natural predators such as arthropods, birds, and mammals) in three oil palm plantations with different weeding practices (i.e., rotational grazing, free-range grazing, and conventional weeding) located on the south-west part of Peninsular Malaysia. We also investigated the effects of site level characteristics on the predation pressures of artificial caterpillars. Across all types of weeding systems, we found that the majority of the predation attempts on the deployed artificial caterpillars were made by arthropods (532 attempts), whereas mammals (66 attempts) and birds (60 attempts) played much smaller roles. Our results showed that predation pressures were consistent across sites indicating that oil palm-cattle integrated plantations (either free-range or rotational grazing systems) would experience similar level of pest control services as conventional herbicide-sprayed plantations. Our results also indicate the influence of site-level habitat variables (i.e., mean of palm heights, canopy cover, and elevation) on predation pressures. Our results suggest that livestock-oil palm integration may sustain natural predation with little or no herbicide input.